Microencapsulation of 2-octylcyanoacrylate tissue adhesive for self-healing acrylic bone cement - Brochu, Alice B. W. (2012)
Here, we report the first phase of developing self-healing acrylic bone cement: the preparation and characterization of polyurethane (PUR) microcapsules containing a medical cyanoacrylate tissue adhesive. Capsules were prepared by interfacial polymerization of a toluene-2,4-diisocyanate-based polyurethane prepolymer with 1,4-butanediol to encapsulate 2-octylcyanoacrylate (OCA). Various capsule characteristics, including: resultant morphology, average size and size distribution, shell thickness, content and reactivity of encapsulated agent, and shelf life are investigated and their reliance on solvent type and amount, surfactant type and amount, temperature, pH, agitation rate, reaction time, and mode of addition of the oil phase to the aqueous phase are presented. Capsules had average diameters ranging from 74 to 222 μm and average shell thicknesses ranging from 1.5 to 6 μm. The capsule content was determined via thermogravimetric analysis and subsequent analysis of the capsules following up to 8 weeks storage revealed minimal loss of core contents. Mechanical testing of OCA-containing capsules showed individual capsules withstood compressive forces up to a few tenths of Newtons, and the contents released from crushed capsules generated tensile adhesive forces of a few Newtons. Capsules were successfully mixed into the poly(- methyl methacrylate) bone cement, surviving the mixing process, exposure to methyl methacrylate monomer, and the resulting exothermic matrix curing.